Ferroptosis’s Master Switch GPX4 emerges as universal biomarker for precision immunotherapy: a pan-cancer study with in vitro experiments validation - Li, Xiao; Zhu, Min; Dong, Ruihua (Frontiers in Oncology, 2025)
IntroductionGlutathione peroxidase 4 (GPX4) is a key enzyme in ferroptosis. Gaining insight into GPX4’s mechanisms and biological roles could offer valuable therapeutic insights for cancer treatment.MethodsBy integrating multi-omics data from The Cancer Genome Atlas (TCGA), the Genotype-Tissue Expression Project (GTEx), cBioPortal, the Human Protein Atlas (HPA), UALCAN, Xiaotao platform and et al., we applied systematic bioinformatics approaches to evaluate the expression, prognostic significance, mutation profiles, DNA methylation and tumor immune microenvironment (TIME) infiltration of GPX4 across diverse cancer types. Furthermore, the role of GPX4 in cell proliferation was experimentally validated.ResultsGPX4 was upregulated in several cancer types. Its potential as a diagnostic biomarker was confirmed by its high reliability in differentiating cancerous from normal tissues, with AUC values surpassing 0.8 in multiple cancers. Functional studies verified its oncogenic function in colorectal and gastric cancer cell lines. In terms of prognosis, GPX4 expression levels were closely associated with overall survival across various cancers. Furthermore, we detected a correlation between the mutation burden of GPX4 across different types of cancer and patient survival outcomes. Additionally, immune infiltration analysis showed significant correlations between GPX4 expression and immune cell presence, particularly macrophages and M2 type macrophages. GPX4 expression also correlated highly with immune modulator pathways and checkpoints. ConclusionCollectively, these pan-cancer analyses underscore the potential of GPX4 as a therapeutic target and biomarker in multiple cancers. Further indepth studies on GPX4’s regulatory mechanisms and clinicopathological significance are warranted to develop novel therapies for the prevention and treatment of human tumors.